Protection of cultural heritage: modern realities and experience of international cooperation - Zhyvohliadova, Daryna (Ukrainian Cultural Studies, 2022)
In the context of the recent full-scale Russian aggression against Ukraine, a global tectonic shift is taking place in the system of political, economic and socio-cultural interaction. New coordinates of cooperation, mutual assistance and support in the international cultural space are being formed. The Russian war against Ukraine, the scale of its cruelty, influenced the world community's awareness of globality, mutual dependence and responsibility for the well-being of humanity as a whole. The creation of strategic alliances for the protection of cultural heritage ensures the stability of the joint path of unique communities, nations, and states to a successful future. The article is aimed at analyzing the modern realities of the protection of the cultural heritage of Ukraine in conditions of war and the experience of international organizations, their cooperation in supporting the uniqueness of Ukrainian culture, the activities of UNESCO and ALIPH as an integral part of a wider management system of international cooperation in supporting unique cultural resources, "unity in diversity".
Keywords: Ukrainian culture; international cooperation; protection of cultural heritage; UNESCO; ALIPH; Russian war against Ukraine